Austeritätspolitik in der Europäischen Währungsunion: Bilanz und Perspektiven - Stefan Homburg; Sebastian Dullien; Martin Höpner; Klaus Schrader; Ronald Schettkat (Wirtschaftsdienst, 2015)
Die Ergebnisse der griechischen Wahlen vom Januar haben deutlich gemacht, dass die betroffene Bevölkerung eine einseitige Politik des Sparens nicht mitträgt. Auch in anderen Krisenländern regt sich Widerstand. Darüber, inwieweit und in welchen Ländern eine Austeritätspolitik durchgeführt wurde und ob sie ökonomisch erfolgreich war, gehen die Auffassungen ebenso auseinander wie über das weitere: Sollte Griechenland aus dem Euro aussteigen oder sind nachhaltigere Strukturreformen erforderlich? – – The authors express different opinions about the outcomes of austerity policies. They do not even agree on the number of states that adopted austerity policies, as measured by deficit and debt ratios. However, most of the authors consider that austerity in Greece has failed due to the lack of political will and the lack of a functioning administration, which obstructs the reform process complementary to austerity policies. Another reason for the failure of austerity policies is probably a delayed and insuffi cient debt restructuring in Greece a lesson which should be taken on board for future adjustment programmes. Apart from economic effects, a continuation of austerity policies in Southern Europe would further damage the social structures and political cultures of the respective countries. Therefore, one author suggests a jointly conducted exit from the eurozone of countries with high effective overvaluations, combined with solidaristic transfers during the period of transition.
Keywords: E62; F45; H63; 330; Haushaltskonsolidierung; Wirkungsanalyse; Wirtschaftliche Anpassung; Griechenland; EU-Staaten